Leverage, Profitabilitas, Likuiditas, Dewan Komisaris, dan Komite Audit terhadap Pengungkapan Sustainable Development Goals - Arin Dwi Wulandari; Eny Kusumawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Sustainable Development Goals (SDGs) is a global agreement to achieve sustainable development. This study aims to analyse the effect of leverage, profitability, liquidity, board of commissioners, and audit committee on SDGs disclosure in non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research uses quantitative methods with secondary data from annual reports and corporate sustainability reports. The measurement of each variable is the sustainability report disclosure index (SRDI) to measure SDGs, the measurement of the leverage variable using the debt to equity ratio (DER), profitability using return on assets (ROA), liquidity using the current ratio, the board of commissioners is proxied by the composition of the independent board of commissioners, and the audit committee is proxied by the number of audit committee members. Data analysis using multiple linear regression. The results showed that leverage has a negative effect on SDGs disclosure, while profitability, board of commissioners, and audit committee have a positive effect. Meanwhile, liquidity has no effect on SDGs disclosure. This study provides recommendations for future research to expand sample coverage and consider other factors that may affect SDGs disclosure, such as material flow cost accounting (MFCA) and financial distress.